Real-time Cell Analysis of the Cytotoxicity of Orthodontic Brackets on Gingival Fibroblasts. Issue 3 (September 2014) - Toy, Ebubekir; Malkoc, Sıddık; Corekci, Bayram; Bozkurt, Buket S.; Hakki, Sema S.
Purpose: The aim of this study was to evaluate the cytotoxic effects of 6 different orthodontic bracket types on human gingival fibroblasts (HGFs) using the xCELLigence system. Methods: The orthodontic brackets used in this study were gold-plated steel (Apollo Gold), titanium (Rematitan), stainless steel (Equilibrium 2), lucid ice (Inspire ICE), metal-reinforced ceramic (Clarity) and composite (OrthoFlex). Gingival fibroblasts were isolated from human gingival connective tissue of systemically healthy individuals. Tested brackets were incubated in DMEM culture medium for 72 hours according to ISO 10993-5 standards. Gingival fibroblasts were maintained with Dulbecco modified Eagle medium containing 10% fetal bovine serum. The xCELLigence system was used to evaluate cell survival. The statistical analysis used was ANOVA and Tukey-Kramer multiple comparison tests. Results: When the data were evaluated in the 30th hour, Apollo Gold showed significant decreases in cell index (P<0.001). It also showed statistically significant decreases (P<0.001) in the 65th hour, but Clarity and Inspire ICE showed significant increases in cell indices (P<0.001, P<0.01). In the 114th hour, Clarity and Equilibrium 2 showed statistically significant increases in cell indices (P<0.001). Inspire ICE and Rematitan demonstrated significant increases (P<0.05). There were significant decreases in cell index of Apollo Gold (P<0.001). Conclusions: The tested brackets are suitable for clinical application, but further studies using different test methods are needed for gold-plated brackets.